An analysis of the influence of international environmental law on international relations: Whaling in the Antarctic case - Nogueira, Sâmara Christina Souza; Miranda, Sarah Clarimar Ribeiro de; Ribeiro, Viviane da Silva; Júnior, Geraldo Uchôa de Amorim; Claus, Roselma Coelho Santa; Silva, Verônica Maria Félix da; Soares, Adriano Luiz do Vale; Nogueira, Jurandy Alves; Huérfano, Johnatan Alfonso Abril (Seven Editora, 2024)
The objective of this study was to analyze the development of International Environmental Law and its influence on international relations and legal order, based on the examination of the case involving Australia’s claim against Japan before the International Court of Justice (ICJ), and in which New Zealand intervened, regarding violations committed by Japan to the International Convention for the Regulation of Whaling (International Convention For The Regulation Of Whaling – ICRW), in which the evolution and modification of the interpretation of the ICRW was verified, which initially aimed only to guarantee the whaling trade, later becoming one of the instruments for the protection of whales and the marine environment. In this sense, this article brought an analysis of the general aspects of classical international law, addressing its concept, instruments and development, as well as its development and the emergence of international environmental law. In this way, the article addressed the main elements about the Convention and the dispute between Australia and Japan, for violations of the ICRW by Japan through its scientific program called JARPA II. It also discussed the decision of the ICJ and the separate vote of the Brazilian judge Antônio Cançado Trindade, who raised the principles of International Environmental Law as possible grounds for application to the case. From there, a general analysis was carried out regarding the influence of international environmental law on International Treaties and Conventions. The methodology used was the deductive method, with a qualitative approach of bibliographic research. It was concluded that there was the development of Classical International Law to Modern International Law, promoting the genesis of International Environmental Law, and this, in turn, has been having a growing development and strengthening, including the emergence of the notion of suprahuman law. Thus, it was found that there was an increase in its scope due to the serious environmental problems that arose with the modern era. Finally, it was concluded that there is an increasing tendency for convergence and unification of general international law and international relations with the principles and norms of international environmental law. DOI:https://doi.org/10.56238/sevened2024.010-028